Implementasi Online Single Submission (OSS) Dalam Pelayanan Perizinan Berusaha Di Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Provinsi Kalimantan Timur - Handayani, Isna Galuh; Rizal, Muhammad (Universitas Medan Area, 2024)
This research focuses on policy implementation through Edward III's communication, resource, disposition and bureaucratic structure approaches. A qualitative descriptive approach by collecting data through interviews, field observations and documentation was carried out in this research. The resource persons in this research were Head of licensing and non-licensing services division of DPMPTSP East Kalimantan Province, OSS operators and several business actors. The data analysis technique used is the interactive model from Miles, Huberman Saldana. Testing the validity and accuracy of data uses source triangulation and technical triangulation. The research results show that the implementation of OSS in business licensing services at the DPMPTSP of East Kalimantan Province in the communication aspect has been carried out, both to implementers and policy targets. In terms of resources, it is quite adequate, although there are still limitations in budget resources and facilities, namely the unstable internet network at certain times. Then, the disposition aspect of OSS implementation has been carried out seriously, where employees as policy implementers or implementers have understood their duties and responsibilities and are committed to implementing the policy. Aspects of the bureaucratic structure are carried out well with the stipulation of Standard Operating Procedures (SOP) through a Governor's Decree and there is fragmentation in the issuance of business permits through OSS.